Ocular surface squamous neoplasia misdiagnosed as corneal opacity and dry eye: a case report - Alaughla, Rime; Manzalji, Kamar; Kadhem, Leena Abdullah; Humaida, Sara; Hassan, Inour A. Nasser; Mohamed Adam, Bayadir Adam (International Journal of Research in Medical Sciences, 2025)
Ocular surface squamous neoplasia (OSSN) represents a spectrum of ocular surface epithelial neoplasms ranging from conjunctival intraepithelial neoplasia (CIN) to invasive squamous cell carcinoma. We report a case of a 75-year-old man initially misdiagnosed with corneal opacity and dry eye, whose symptoms persisted despite lubricant therapy. Detailed ophthalmic examination revealed a suspicious lesion extending across the temporal cornea with sentinel vessels and corneal invasion. Histopathological analysis confirmed high-grade intraepithelial dysplasia consistent with CIN, while immunohistochemistry for p16 was negative. The patient underwent surgical excision with wide margins, adjunctive cryotherapy, and postoperative topical 5-fluorouracil therapy. This case illustrates the diagnostic challenges of OSSN due to its ability to mimic benign ocular surface conditions. Prompt recognition, appropriate histopathological confirmation, and timely treatment are essential to prevent progression and preserve vision. Clinicians should maintain a high index of suspicion for atypical or persistent ocular surface lesions, particularly in elderly patients with risk factors such as ultraviolet exposure and diabetes.